Translating Blackness : Latinx colonialities in global perspective - García Peña, Lorgia, 1978- (Duke University Press, 2022)
"Translating Blackness examines the relationship between race, migration, and colonialism through the lives, works, and epistemologies of Black Latinx people across diasporas. Lorgia García-Peña presents Black Latinidad as a social, cultural, and political formation that produces new approaches, knowledges, and ways of understanding our present world. Central to Translating Blackness is the concept of vaivén (coming and going). The term vaivén denotes the crossings-forth and back-that shape migrant life and expose the limits of the binary oppositions through which human beings are deployed as either citizens or foreigners. Vaivén also refers to the nations which oscillate between empire and country, receiving or expulsing people from its center. Black Latinx peoples, García-Peña argues, are subjects in vaivén between belonging and unbelonging. Their lived experience reveals that the nation is not a sufficient rubric from which to understand human experiences."--